2020
DOI: 10.1186/s12917-020-02537-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and phylogenetic analysis of hepatitis E virus in pigs in Vietnam

Abstract: Background Hepatitis E virus (HEV) is a zoonotic disease and has been reported around the world. The main objective of this study was to evaluate the sero-prevalence and phylogenetic analysis of HEV in Vietnam. Pig blood and fecal pooled samples were collected to assess the prevalence of HEV. We assessed the true prevalence (TP) of HEV from apparent prevalence (AP) by taking into account the sensitivity and specificity of diagnostic tests using a Bayesian approach. For phylogenetic analysis, the data compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…As with pig’s livers, viral RNA has also been sporadically (1.8%) found in pig’s blood, (Geng et al, 2019 ), and sera (6.7%) of slaughtered animals (Garcia et al 2020 ), despite the virus being highly prevalent (23.4–100%) in blood and blood-derived by-products such as haemoglobin, fibrinogen and plasma (Boxman et al, 2017 ; Geng et al, 2019 ). Differences in virus occurrence in edible blood between studies may stem from differences observed between countries in natural virus prevalence in pigs (Berto, Backer, et al, 2012 ; Di Bartolo et al, 2008 ; Lee et al, 2020 ) and the age of slaughtered animals, as the likelihood of viraemia increases in younger pigs (Meng et al, 1997 ; Sooryanarain et al, 2020 ; Wu et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…As with pig’s livers, viral RNA has also been sporadically (1.8%) found in pig’s blood, (Geng et al, 2019 ), and sera (6.7%) of slaughtered animals (Garcia et al 2020 ), despite the virus being highly prevalent (23.4–100%) in blood and blood-derived by-products such as haemoglobin, fibrinogen and plasma (Boxman et al, 2017 ; Geng et al, 2019 ). Differences in virus occurrence in edible blood between studies may stem from differences observed between countries in natural virus prevalence in pigs (Berto, Backer, et al, 2012 ; Di Bartolo et al, 2008 ; Lee et al, 2020 ) and the age of slaughtered animals, as the likelihood of viraemia increases in younger pigs (Meng et al, 1997 ; Sooryanarain et al, 2020 ; Wu et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fecal samples were collected from 200 pigs and the liver samples were collected from 60 pigs slaughtered in Ulaanbaatar city. The ORF2 region of HEV RNA was a target sequence for viral detection [21]. In addition, the farmers were asked questions that included general knowledge about HEVs and possible contact between livestock to analyze risk factors.…”
Section: Samplingsmentioning
confidence: 99%
“…RNA was precipitated with 0.5 mL isopropanol and washed with 1 mL of 75% ethanol. The RNA was solubilized in 20 µL RNase-free water [21]. A one-step RT-PCR kit (QIAGEN, Hilden, Germany) was used to amplify the ORF2 region of the HEV (primer sequences used: ORF2-F1; (5772-5794) 5 -AATTATGCYCAGTAYCGRGTTG-3 , ORF2-R1; (6416-6439) 5 -CCCTTRTCYTGCTGMGCATTCTC-3 ).…”
Section: Rna Extraction and Detection Of Hev Rna By Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies of the Vietnamese population have revealed a high anti-HEV IgG seroprevalence in healthy individuals (31%), in chronic hepatitis B virus (HBV) patients (45%), and among occupational workers exposed to pigs (53%) [ 4 , 14 , 15 ]. Despite the possibility of such serious outcomes, the scale of HEV infection during pregnancy, and of potential maternal, fetal, and neonatal complications, has not been investigated in resource-poor settings where the prevalence of HEV infection is expected to be high.…”
Section: Introductionmentioning
confidence: 99%